Diffuse alveolar hemorrhage syndrome secondary to bocavirus and rhinovirus infection in a pediatric patient - Lasso, Ruben Eduardo; Concha, Sandra patricia; Agudelo, Maria Teresa; Reina Céspedes, Carlos Eduardo (CES Medicina, 2017)
The diffuse alveolar hemorrhage syndrome is characterized by the presence of blood in the pulmonary alveolus from arterioles, venules and pulmonary capillaries, as a consequence of the lesion of the alveolar wall and without an endobronchial alteration. Its presentation includes a classic triad of hemoptysis, anemia and diffuse alveolar infiltrates. It´s a rare but potentially fatal entity and there are no clear data on its real incidence in the pediatric population. We present the case of a previously healthy pediatric patient, immunocompetent, who presented diffuse alveolar hemorrhage syndrome with secondary ventilatory failure. After discarding all possible etiologies, coinfection by Rhinovirus and human Bocavirus was detected through the polymerase chain reaction, determining them as causal factors of the event. Recently, viral infections have been postulated as causing serious lung disease, especially coinfection in immunocompromised patients, in this case Rhinovirus and human Bocavirus; however there are no reports on the syndrome caused by these viruses. DOI: http://dx.doi.org/10.21615/cesmedicina.32.1.6